The hyponatremic patient: a systematic approach to laboratory diagnosis - Milionis, Haralampos J. (2002)
HYPONATREMIA (SERUM SODIUM LEVEL LESS THAN 134 MMOL/L) is a common electrolyte disturbance. Its high prevalence and potential neurologic sequelae make a logical and rigorous differential diagnosis mandatory before any therapeutic intervention. A history of concurrent illness and medication use as well as the assessment of extracellular volume status on physical examination may provide useful clues as to the pathogenesis of hyponatremia. Measurement of the effective serum tonicity (serum osmolality less serum urea level) is the first step in the laboratory evaluation. In patients with normal or elevated effective serum osmolality (280 mOsm/kg or greater), pseudohyponatremia should be excluded. In the hypo-osmolar state (serum osmolality less than 280 mOsm/kg), urine osmolality is used to determine whether water excretion is normal or impaired. A urine osmolality value of less than 100 mOsm/kg indicates complete and appropriate suppression of antidiuretic hormone secretion. A urine sodium level less than 20 mmol/L is indicative of hypovolemia, whereas a level greater than 40 mmol/L is suggestive of the syndrome of inappropriate antidiuretic hormone secretion. Levels of hormones (thyroid-stimulating hormone and cortisol) and arterial blood gases should be determined in difficult cases of hyponatremia.